Sleep and its relationship to health in parents of preterm infants: a scoping review - Gunhild Nordbø Marthinsen (BMC Pediatrics, 2018)
Abstract Background Sleep is essential for human health and functioning. Parents of preterm infants are susceptible to sleep disturbances because of stress related to the preterm birth. Poor sleep has the potential to affect parental health and well-being. The aim of this study was to identify and map evidence on sleep and its relationship to health in parents of preterm infants. No review has summarized the evidence on this topic. Methods A scoping review was conducted. Seven health and medical electronic research databases were searched for relevant quantitative and qualitative primary studies, including grey literature. The search was performed March 2–7, 2017. Results Ten American studies and one Australian study were included in the review. Most research was quantitative and focused on maternal sleep and mental health within the first two weeks after the childbirth. Both objective and subjective sleep measures were used to study sleep at the hospital; actigraphs were not used after discharge. Maternal sleep was poor early postpartum, and this was associated with negative health outcomes. Two cohort studies compared sleep in mothers of preterm and term infants, but the results were conflicting. In one qualitative study, fathers described their inability to catch up on sleep after homecoming with a preterm baby. Conclusions Quantitative studies reporting on maternal sleep early postpartum was most frequently occurring in the results. Qualitative research on the topic was identified as a knowledge gap. More cultural and geographical breadth, including research on fathers’ sleep, is recommended in future research.